Comparison of surgical outcomes of C1-2 fusion surgery between O-arm-assisted operation and C-arm assisted operation in children with atlantoaxial rotatory fixation - Zhou, Xin; Yang, Yue Benny; Meng, Yichen; Lin, Tao; Zhou, Xuhui; Wang, Ce (Frontiers in Pediatrics, 2023)
Objective Placement of the pedicle screw is technically challenging during C1-2 fusion surgery in children and different intraoperative image-guided systems have been developed to reduce the risk of screw malposition. The purpose of the present study was to compare surgical outcomes between C-arm fluoroscopy and O-arm navigated pedicle screw placement in the treatment of atlantoaxial rotatory fixation in children. Methods We retrospectively evaluated charts of all consecutive children with atlantoaxial rotatory fixation who underwent C-arm fluoroscopy or O-arm navigated pedicle screw placement from April 2014 to December 2020. Outcomes including operative time, estimated blood loss (EBL), accuracy of screw placement (Neo's classification) and completed fusion time were evaluated. Results A total of 340 screws were placed in 85 patients. The accuracy of screw placement of the O-arm group was 97.4%, which was significantly higher than that of the C-arm group (91.8%). Both groups had satisfied bony fusion (100%). Statistical significance (230.0 ± 34.6 ml for the C-arm group and 150.6 ± 47.3 ml for the O-arm group, p < 0.05) was observed with respect to the median blood loss. There were no statistically significant difference (122.0 ± 16.5 min for the C-arm group and 110.0 ± 14.4 min for the O-arm group, p = 0.604) with respect to the median operative time. Conclusion O-arm-assisted navigation allowed more accurate screw placement and less intraoperative blood loss. Both groups had satisfied bony fusion. O-arm navigation did not prolong the operative time despite the time required for setting and scanning.